JWST’s Sharper View of EX Lup: Cold Water from Ice Sublimation during Accretion Outbursts - Sarah A. Smith; Carlos E. Romero-Mirza; Andrea Banzatti; Christian Rab; Péter Ábrahám; Ágnes Kóspál; Rik Claes; Carlo F. Manara; Karin I. Öberg; Jeroen Bouwman; Fernando Cruz-Sáenz de Miera; Joel D. Green (The Astrophysical Journal Letters)
The unstable accretion phases during pre-main-sequence evolution of T Tauri stars produce variable irradiation and heating of planet-forming regions. A strong accretion outburst was observed with Spitzer-InfraRed Spectrograph in 2008 in EX Lup, the prototype of EXor variables, and found to increase the mid-infrared water and OH emission and decrease organic emission, suggesting large chemical changes. We present here two JWST-MIRI epochs of quiescent EX Lup in 2022 and 2023 obtained over a decade after the 2008 outburst and several months after a moderate burst in 2022. With JWST’s sharper spectral view, we can now analyze water emission as a function of temperature in the two MIRI epochs and, approximately, also in the previous Spitzer epochs. This new analysis shows a strong cold water vapor “burst” in low-energy lines during the 2008 outburst, which we consider clear evidence for enhanced ice sublimation due to a recession of the snowline, as found in protostellar envelopes. JWST shows that EX Lup still has an unusually strong emission from cold water in comparison to other T Tauri disks, suggesting >10 yr long freeze-out timescales in the inner disk surface. EX Lup demonstrates that outbursts can significantly change the observed organic-to-water ratios and increase the cold water reservoir, providing chemical signatures to study the recent accretion history of disks. This study provides an unprecedented demonstration of the chemical evolution triggered by accretion outbursts in the class II phase and of the high potential of time-domain experiments to reveal processes that may have fundamental implications on planet-forming bodies near the snowline.